Integration of Balanced Scorecard and Analytical Hierarchy Process as a Method of Performance Measurement and Target Strategy Selection - Siagian, Wesly Mailander; Togatorop, Iqnatius Cahyo H (Universitas Bina Sarana Informatika, 2025)
This study evaluates the performance of PT. XYZ, a prominent ready-mix concrete company in Toba Regency, North Sumatra, Indonesia, from 2018 to 2022. Utilizing a descriptive and quantitative research approach, data were gathered through document analysis, questionnaires, and interviews. The findings reveal significant financial weaknesses, particularly in the total asset turnover, return on investment (ROI), and debt-to-asset ratios. However, the company demonstrates strong performance in customer satisfaction, internal business processes, and learning and growth dimensions. Employing the Balanced Scorecard (BSC) framework, this research assesses these four perspectives and highlights the critical importance of the learning and growth perspective for strategic development. Through the integration of the Analytical Hierarchy Process (AHP), the study identifies the enhancement of information systems as a key strategic goal. This approach not only provides a comprehensive evaluation of PT. XYZ's performance over the five-year period but also offers targeted recommendations for future business development and sustainable growth.